Off-line magnetic resonance imaging navigation of cervix cancer brachytherapy in patients with risk factors for uterine perforation - Al-Hammadi, Noora Mohammed; Chandramouli, Suparna Halsnad; Hammoud, Rabih; Petric, Primoz (Journal of Contemporary Brachytherapy, 2017)
Purpose : There are no reports on pre-insertion identification of cervix cancer patients at risk for uterine perforation during brachytherapy (BT). Our aim was to assess the incidence of risk factors in our patient cohort, and assess feasibility of a novel technique of magnetic resonance imaging (MRI)-guided navigation for applicator insertion (NAI) in high-risk cases. Material and methods : All patients with locally advanced cervical cancer, treated with image guided adaptive BT at our department between October 2013 and June 2017 were considered for analysis. Tumor characteristics on initial MRI (MRI initial ), pre-BT MRI (MRI pre-BT ), and BT MRI (MRI BT ) were assessed. Frequency of risk factors (age above 60 years, retroverted/retroflected uterus, tumor necrosis, non-visible cervical orifice, distorted cervical canal) was recorded. Patients with two or more factors underwent MRI guided NAI. Time needed for NAI was estimated and procedure feasibility score assigned using a three-tiered scoring system. Results : Twenty-seven patients (98 insertions) were included. Mean tumor volume was 70.2 (± 47.9), 17.8 (± 18.9), and 10.3 (± 9.1) cm3 on MRI initial , MRI pre-BT , and MRI BT 1, respectively (p < 0.05). In 16 (59%) cases, ≥ 1 perforation risk factor was found on MRI pre-BT : distorted canal in 12 (44%), necrosis in 9 (33%), retroverted/retroflected uterus in 8 (30%) cases. Nine (33%) patients had ≥ 2 risk factors and underwent MRI guided NAI. Additional time to perform NAI was estimated at 105 minutes, and feasibility score was 1 in all cases. There were no cases of uterine perforation. Conclusions : Using pre-insertion MRI, we found ≥ 2 risk factors for uterine perforation in 1/3 of patients. Off-line MRI navigation was feasible and enabled non-complicated insertion in all cases. Further studies with larger sample size are warranted to assess its clinical efficacy.